The Effects of Regional Hydrologic Alteration on Fish Community Structure in Regulated Rivers. (18th December 2015) - Macnaughton, Camille J.; McLaughlin, Fraser; Bourque, Guillaume; Senay, Caroline; Lanthier, Gabriel; Harvey‐Lavoie, Simonne; Legendre, Pierre; Lapointe, Michel; Boisclair, Daniel
Abstract: Alterations to temporal patterns of river flow regimes resulting from damming and flow regulation practices may have negative consequences for freshwater communities. However, little has been performed to develop a holistic approach to assess the effects of hydrologic alterations on fish communities across a wide range of rivers and between different regulation strategies. To address this, we used daily and hourly hydrologic data from gauges in 10 regulated and 14 unregulated Canadian rivers. Building on the Ecological Limits of Hydrologic Alteration concept, hydrologic alterations for many ecologically relevant flow indices were combined to obtain river‐specific hydrologic alteration scores. Extensive community surveys to estimate fish abundance, biomass, diversity indices and habitat guild representation provided data for the derivation of similar river‐specific biotic alteration scores relative to unregulated river conditions. Our results indicate that biological impairment consisting of significant biotic alteration relative to the means from unregulated rivers was directly related to increasing flow alteration scores, with the smallest fish and flow alteration scores observed in run‐of‐river systems and the greatest alteration scores under hydro‐peaking regimes. Our approach not only examined the relationship between river‐specific hydrologic alteration scores and the associated biotic responses, but also provided a more comprehensive assessment of the flow‐response alteration relationship between regulation practices, which may better inform future environmental flow management guidelines. Copyright © 2015 John Wiley & Sons, Ltd.